Improvement of SiC/PyC coating on mechanical and anti-oxidation properties through biomimetic laminated structure design. (December 2022) - Chen, Guohui; Zhang, Yulei; Zhang, Pengfei; Fu, Yanqin; Gai, Wenhan; Kong, Jing'an
Abstract: To improve fracture toughness and oxidation resistance of SiC coating, we designed and prepared a SiC/PyC laminated coating with biomimetic laminated structure on carbon/carbon (C/C) composites by chemical vapor deposition (CVD) method. The microstructure, mechanical properties and oxidation resistance of the coating were investigated. The results showed that the laminated structure could effectively improve the toughness of SiC coating and avoid the formation of penetrating cracks, thus improved the oxidation resistance of coating. The weight loss of laminated SiC/PyC coated sample decreased 75.2 % compared with that of single SiC coated sample after oxidation at 1773 K. The good oxidation resistance and mechanical properties of SiC/PyC laminated coating were attributed to the toughening effect of laminated structure including crack deflection and interface debonding. Our work could bring beneficial enlightenment to improve the toughness of ceramic coating. Highlights: A SiC/PyC laminated coating with biomimetic laminated structure was prepared on carbon/carbon (C/C) composites by chemical vapor deposition (CVD) method. The laminated structure can effectively improve the toughness of SiC coating and avoid the formation of penetrating cracks. The weight loss of laminated SiC/PyC coated sample decreased 75.2% compared with that of single SiC coated sample after oxidation at 1773 K. The good oxidation resistance and mechanical properties of SiC/PyC laminated coating was attributed to the toughening effect of laminated structure including crack deflection and interface debonding.